El Portal 1933-04 (April 1933) - San Jose State College:::Creator::::::::::::
Volume 2, number 5. El Portal was a monthly literary magazine published by the English Department featuring student writing. The genres include fiction, poetry, and essays. This is the second incarnation of the literary journal The Quill, which in turn becomes Reed Magazine in 1948.